1998
DOI: 10.1111/ppa.1998.47.6.749
|View full text |Cite
|
Sign up to set email alerts
|

Role of root disease in the poor establishment of Medicago pastures after cereal cropping in South Australia

Abstract: Field experiments were conducted in 1991, 1992 and 1994 at three locations in South Australia to investigate the involvement of root pathogenic fungi in the poor establishment and growth of annual medics (Medicago spp.) in naturally regenerating pastures. The severity of root disease across the three sites, rated on a 0–4 scale, was 2·4 (1991), 2·7 (1992) and 1·7 (1994). Medicago emergence and/or herbage production increased in the presence of potassium phosphonate applied as a soil drench or as a postemergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Conversely, Fusarium spp. found in wheat contributed to root rot and poor establishment of subsequent legume-based pastures (Pankhurst et al 1998). Satyaprasad et al (1997) found that pathogenicity of F. avenaceum to potato tubers was not related to the plant species from which the isolates originated.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, Fusarium spp. found in wheat contributed to root rot and poor establishment of subsequent legume-based pastures (Pankhurst et al 1998). Satyaprasad et al (1997) found that pathogenicity of F. avenaceum to potato tubers was not related to the plant species from which the isolates originated.…”
Section: Resultsmentioning
confidence: 98%
“…Strains of F. avenaceum are commonly implicated as causal agents of root rot and wilt in forage crops (Miller-Garvin and Viands 1994;Pankhurst et al 1998;Sivasithamparam 1993). In addition, various strains of F. avenaceum are also frequently isolated from asymptomatic alfalfa (Pegg and Parry 1983) and red clover plants (R.D.…”
Section: Resultsmentioning
confidence: 99%
“…The role of R. solani in reducing the establishment of pasture legumes in Australia was demonstrated by Pankhurst et al (1998). Given the presence of AG-2-2 on several hosts in Queensland and in the temperate regions of southern Australia, it is likely that the pathogen will have an impact on the establishment and persistence of sulla in some areas, unless resistant or tolerant cultivars are developed.…”
Section: Discussionmentioning
confidence: 99%